Bersanding dalam resepsi perkawinan:refleksi atas pandangan dan perilaku hukum di Kota Palangka Raya - Abdul Helim (State Institute of Islamic Studies (IAIN) Salatiga, 2011)
According to the seven marriage couples and three fatwa givers which become of the subjects of thestudy, the mixture of the place for the bride and the groom is prohibited (haram) because it can provokefitnah, there is tabarruj, ask for the highest bride price, focus more on the gifts, and money from theguests and the other people who spread out the yellow rice. The doers don’t know the legal argumentsand even taqlid to the fatwa givers but they don’t have reliable arguments. The doers only argue that lifeof men and women should be separated as in salat and there is no nas that allows the bride and thegroom to sit next to each other. Ikhtilat is allowed to do in the market or workplace because was practicedduring prophet Muhammad SAW’ life. This argument is weak and hard to accept and it traps us becausethere is a great potency of disadvantage between Ikhtilat in the market and work place compared toIkhtilat in wedding reception.